Global stabilization of switched control systems with time delay - Zhang, Y.; Wang, M.; Xu, Honglei; Teo, Kok Lay (Elsevier, 2014)
In this paper, the stabilization problem of switched control systems with time delay is investigated for both linear and nonlinear cases. First, a new global stabilizability concept with respect to state feedback and switching law is given. Then, based on multiple Lyapunov functions and delay inequalities, the state feedback controller and the switching law are devised to make sure that the resulting closed-loop switched control systems with time delay are globally asymptotically stable and exponentially stable.